Implementasi Prinsip-Prinsip Asuransi Syariah Pada Pt. Prudential Syariah Binjai - Hernita, Hernita; Lubis, Fauzi Arif (Bata Ilyas Educational Management Review, 2023)
This research is motivated by the large number of insurers who use sharia practices so that their development remains in line with sharia principles, so, according to the author, it is very important to study the concept of applying sharia principles when it is related to the problems that exist at this time. PT. Prudential Syariah Binjai Branch is an insurance company with a vision to help people get the best in life and a mission to provide protection to the community through life insurance and health insurance products. The purpose of this research is to find out the principles of Islamic insurance at PT. Prudential Syariah Binjai Branch. This study uses a qualitative approach using a case study approach of observation and interviews. The type of data used in this study includes primary data and secondary data. Primary data from interviews and observations. Secondary data was obtained from insurance-related books and journals. This research was conducted at PT. Prudential Syariah Binjai branch. The results of the study show that the implementation of Islamic insurance in Islamic insurance in Binjai is in accordance with the principles of Islamic general insurance. The emergence of sharia insurance in the Islamic world is based on the assumption that conventional insurance contains elements of gharar, usury and maisir. As for Sharia Insurance itself, it has principles in the Al-Quran and Hadith, namely helping each other and having a sense of security.